A Deixis Analysis of Song Divide by Ed Sheeran - Aini, Nurul; Az-Zihra. T, Khoirunniswa; Ramadhani, Shella Fitri; Rezky Wulan, Rezky Wulan; Sukma Dara, Emeliya (e-Journal of Linguistics; Vol 17 No 1 (2023): ejl-January, 2022)
The purpose of this research is to identify the type of Deixis and find the type of Deixis that is generally mastered in the lyrics of the song Ed Sheeran Divide. This includes the type of qualitative research. This research uses observation method. The data collection method uses listening & analyzing the song Divide by Ed Sheeran. The results of this study found that all types of deixis were direct (68 dates ), location (4 dates), & time (1 dates). Deixis is included on the lyrics to Ed Sheeran's song Divide. People's deixis is often found in Ed Sheeran's Divide lyrics. The most common types of deixis found in this study were me and people deixis, such as me. The most generic plural deixis is Sie using loose 20. Deixis serves to tell the role contained in the lyrics. The effect of using Person Deixis is to choose who is referred to in song lyrics. Locale deixis is used to tell where or where the lyric incident took place.The effect of local deixis is to create the same interpretation of the location of the incident in the song lyrics. Deixis when used in the lyrics to tell when the incident occurred. The effect according to clock deixis is to emphasize that an incident has occurred or has already occurred.